(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
The following work defines a modern compositive language developed and implemented by Cesar Francisena in one of his most unique works for Chamber Music Trío de las Proporciones para flauta, clarinete y piano. The objective is to conduct an interpretive - analytical study of his work. Franchisena was born in Chaco (Argentina) on September the 3rd of 1923 and died in Cordoba on January the 1st of 1992. He was of the most distinguished members of the “New Music Association” (ANM). He led the Cordoba Branch from where he disseminated a large part of his contemporary repertoire (national and international). His work began to get known in Argentina in the fifties. He started at the Art Faculty of the National University in 1956 and kept working there for more than three decades. Founder of Compositions I, II and III Lecturers and Chief Founder of the Electronic Lab (1977) and Distinguished Professor Emeritus (1992). Franchisena paired to the European and American compositive lines representing the local Avant Gard. This statement is backed up for how he used different variables such as space and times, emphasizing the usage of different articulations, densities and structures.